Application of Combined Self-Surrender Exercises and Deep Breath Relaxation to Lower Blood Sugar Levels Elderly Diabetes Mellitus Type - Eva Susanti; Rizki Sri Haryanti; Jawiyah Jawiyah (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Diabetes is already considered an epidemic and by 2025, it is estimated that around 380 million people, or 7.3% of the adult population in the world will be affected by this disease Diabetes Atlas 2012 (International Diabetes Federation) lists that the estimated population of Indonesia over 20-79 years is 7.6 million people and the assumption of DM prevalence is 5.14%. Indonesia ranks 8th largest in the number of people with diabetes mellitus. The order above is China (92.3 million), India (63.0 million), the United States (24.1 million), Brazil (13.6 million), the Russian Federation (12.7 million), and Mexico (10.6 million). Problems faced by elderly Posyandu participants In the working area of the Kerinjing Health Center, Kerinjing Village, Ogan Ilir Regency, Palembang.: Never received information about Diabetes Mellitus and non-pharmacological management, especially the combination of self-surrender exercises with deep breath relaxation to lower blood sugar in the elderly with Diabetes Mellitus, Never been taught self-surrender exercises and deep breath relaxation in lowering blood sugar levels in the elderly Diabetes Mellitus At the Elderly Posyandu, the working area of the Kerinjing Health Center is Kerinjing Village, Ogan Ilir Regency, Palembang. The approach methods used to achieve the Output Target are determined, namely; Education (Counseling), Demonstration of Self-Resignation Training, and Deep Breath Relaxation in Lowering Blood Sugar Levels of Diabetes Mellitus Elderly. The application of the Combination of Self-Resignation Exercises and Deep Breath Relaxation is carried out routinely in the elderly with Diabetes Mellitus there is a decrease in Blood Sugar levels by involving cadres and elderly families who control the implementation of the exercise.